2006
DOI: 10.1002/elan.200603535
|View full text |Cite
|
Sign up to set email alerts
|

Interdigitated Conductometric Immunosensor for Determination of Interleukin‐6 in Humans Based on Dendrimer G4 and Colloidal Gold Modified Composite Film

Abstract: A highly sensitive, fast and stable conductometric immunosensor for determination of interleukin-6 (IL6) in humans is developed by encapsulation of horseradish peroxidase-labeled interleukin-6 antibody (HRP-anti-IL6) in poly(amidoamine) fourth-generation dendrimer (dendrimer) and colloidal gold (nanogold) modified composite architecture. The presences of nanogold and dendrimer provided a congenial microenvironment for the immobilized biomolecules and decreased the electron transfer impedance, leading to a dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 24 publications
(15 reference statements)
0
18
0
1
Order By: Relevance
“…The lower limit of detection (LLD, 3STD) of IL-6 was determined to be 0.29 pg ml -1 for TMB detection and 0.13 pg ml -1 for luminol detection (Table 1). In literature, various methods have been developed for determination of IL-6 levels, such as microfluidic immunosensor, [22a] conductometric immunosensor, [8b] microsphere-based immunoassay [52] and capacitive biosensor [53] with varying detection limits. Dendrimer based assay in present study has a detection limit superior to that of other previously reported IL-6 assay except that obtained by Johansson et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lower limit of detection (LLD, 3STD) of IL-6 was determined to be 0.29 pg ml -1 for TMB detection and 0.13 pg ml -1 for luminol detection (Table 1). In literature, various methods have been developed for determination of IL-6 levels, such as microfluidic immunosensor, [22a] conductometric immunosensor, [8b] microsphere-based immunoassay [52] and capacitive biosensor [53] with varying detection limits. Dendrimer based assay in present study has a detection limit superior to that of other previously reported IL-6 assay except that obtained by Johansson et al .…”
Section: Resultsmentioning
confidence: 99%
“…[5] In addition, dendrimers can have a larger area of capture than linear analogs with consequently high capture probability. Dendrimers have been utilized in dip-pen nanolithography, [6] DNA and protein arrays, [7] nanocatalyst-based electrochemical immunosensor, [8] biosensor-based on dendrimer encapsulated Pt nanoparticles [9] and regenerable affinity biosensing surfaces. [10] Recent work on a glass surface coated with a polyamidoamine dendrimer terminated with carboxylic acid group (PAMAM-COOH), showed that the dendrimer-modified surface had relatively low nonspecific cellular protein adsorption, and can also enable antibody binding.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the sensitive part of each electrode was about 1 mm 2 . The schematic diagram of the interdigitated transducer is described in previous report [13].…”
Section: Design Of Interdigitated Conductometric Immunosensormentioning
confidence: 99%
“…Conductometric immunoassays with highly specific molecular recognition of antigens by antibodies have become important analytical tools in clinical and biochemical analyses and for monitoring of environment and food quality control, since it is highly sensitive, low cost, low power requirements, and has high compatibility with advanced micromachining technologies [8][9][10][11][12]. Moreover, the technology has been developed for the detection of interleukin-6 by using an interdigitated conductometric immunosensor in our report previously [13].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been used to detect the level of IL-6 in diseased tissues including enzyme-linked immunosorbent assay (ELISA) [10], fluorescent sensor [11], conductometric immunosensor [12], chemiluminescence immunoassay [13], fluorescence-based fiber-opticbiosensors [14] and electrochemical immunosensor [6,15]. However, sophisticated instrumentation and relatively low limits of detection (LODs) for these methods restrict their further application for detecting early stage disease in real samples.…”
Section: Introductionmentioning
confidence: 99%